2018
DOI: 10.1111/jdv.15325
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of IgG subclasses and complement deposition in BP230‐type bullous pemphigoid

Abstract: Background Bullous pemphigoid (BP) is the most common autoimmune blistering disease. BP180 is the primary autoantigen of BP, and in a portion of BP cases, BP230 is the only target of autoantibodies. Such BP is called BP230‐type BP. BP230‐type BP tends to show milder clinical phenotypes than conventional BP, but the reason is unclear. The pathogenic roles of autoantibodies and complement activation have been shown in conventional BP, but the distribution of IgG subclasses and the degree of complement deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…These studies support the dominant role of anti-BP180 autoantibodies compared with anti-BP230 autoantibodies in the pathogenesis of BP. There are approximately 8% of BP cases where only anti-BP230 antibodies are found, and this is referred to as BP230-type BP [ 136 ].…”
Section: Bullous Pemphigoidmentioning
confidence: 99%
“…These studies support the dominant role of anti-BP180 autoantibodies compared with anti-BP230 autoantibodies in the pathogenesis of BP. There are approximately 8% of BP cases where only anti-BP230 antibodies are found, and this is referred to as BP230-type BP [ 136 ].…”
Section: Bullous Pemphigoidmentioning
confidence: 99%
“…Antibodies that target BP 180 at the NC16A domain result in inflammatory BP but non‐NC16A targets result in a non inflammatory presentation, where there is an absence of urticaria and erythema . The BP230 subtype of BP, where the BP 230 is the only autoantigen targeted, typically presents with milder disease than the classic BP . Classically, patients have weeks to months of pruritus, urticaria or eczema followed by symmetric tense bullae on urticated, erythematous or normal skin on the trunk, inner thigh and flexures.…”
Section: Bullous Pemphigoidmentioning
confidence: 99%
“…23 The BP230 subtype of BP, where the BP 230 is the only autoantigen targeted, typically presents with milder disease than the classic BP. 24 Classically, patients have weeks to months of pruritus, urticaria or eczema followed by symmetric tense bullae on urticated, erythematous or normal skin on the trunk, inner thigh and flexures. Atypical presentations include an absence of blisters in up to 20% of cases, chronic itch with urticaria or eczematous eruptions, prurigo nodules and excoriations (Figs.…”
Section: Uv Light Radiation and Infections Such As Human Herpes Virumentioning
confidence: 99%
“…Based on these findings, it is reasonable to speculate that some triggers of BP may induce the release of autoantibodies against BP180 epitopes other than NC16A. And the presence of anti-BP230 antibodies brings several particular clinical features of BP (63). However, the aforementioned studies have demonstrated that patients who lacked anti-BP230 antibodies were prone to mucosal lesions (13).…”
Section: Mechanisms Of Mucosal Involvementmentioning
confidence: 98%